Description of Harpactea popovi sp. n. from Bulgaria with further taxonomic notes on related species (Araneae, Dysderidae) - Dimitrov, Dragomir; Deltshev, Christo; Lazarov, Stoian (Zootaxa, 2019)
Harpactea popovi sp. n. is described and illustrated based on males. It was collected in beech forest habitats (Fagus orientalis) in Strandzha Mountain, Southeastern Bulgaria. The new species belongs to the Harpactea rubicunda species group as defined by Deeleman-Reinhold (1993) and is closely related to H. ice Komnenov & Chatzaki, 2016 and H. sturanyi (Nosek, 1905). The following synonymies were established: H. camenarum Brignoli, 1977 = H. sturanyi (Nosek, 1905) syn. n., H. lyciae Brignoli, 1978 = H. sturanyi (Nosek, 1905) syn. n. New illustrations and photographs for the discussed species are also presented.